PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KEPUTUSAN INVESTASI DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Luluk Larasati; Muhammad Fachruddin Arrozi (Globalwriting Academica Consulting & Publishing, 2022)
The purpose of this study is to obtain empirical evidence of the influence of the variables of Corporate Social Responsibility (CSR), Investment Decisions, and Capital Structure on Company Value in mining companies listed on the IDX for the period 2018-2021. This research design is included in causal associative research. The population of this study are mining companies listed on the Indonesia Stock Exchange for the period 2018- 2021. Sample selection through purposive sampling method. There are 13 companies that meet the criteria as the research sample so that the observation data is 52. The analytical method used is the Multiple Linear Analysis method. The results show that simultaneously Corporate Social Responsibility, Investment Decisions, and Capital Structure have a significant influence on Firm Value (Tobin's Q). Investment decisions that are proxyed with Price Earning Ratio (PER) have a significant effect on Firm Value (Tobin's Q). Meanwhile, Capital Structure through DER has a negative and insignificant effect on firm value. And Corporate Social Responsibility does not have a significant effect on Firm Value (Tobin's Q) partially.